2020
DOI: 10.1177/0032885520916820
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Inmates’ Positive Attitudes toward Participating in a Restorative Justice Process: The Effects of a Victim Awareness Process

Abstract: In the present study, we conducted an empirical experiment to examine whether exposure to a victim awareness procedure would affect inmates’ attitudes toward participating in a restorative-justice process. In addition, the study sought to evaluate whether there are differences between inmates serving their sentences in prisons with different therapeutic orientations. The findings indicate that participants who were exposed to a victim awareness procedure were more aware of the harm caused to the victim and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Overall, our findings complement the body of literature focusing on alternative implementation methods of RJIs and suggest lack of dialogue does not preclude benefits of increasing victim awareness. Focusing future research on how to intertwine non-dialogue based RJIs with face-to-face dialogue or other interventions may also help reduce recidivism after release from prison, consistent with the increased willingness to engage in restorative dialogue found by Weimann-Saks & Peleg-Koriat (2020).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Overall, our findings complement the body of literature focusing on alternative implementation methods of RJIs and suggest lack of dialogue does not preclude benefits of increasing victim awareness. Focusing future research on how to intertwine non-dialogue based RJIs with face-to-face dialogue or other interventions may also help reduce recidivism after release from prison, consistent with the increased willingness to engage in restorative dialogue found by Weimann-Saks & Peleg-Koriat (2020).…”
Section: Discussionmentioning
confidence: 75%
“…Yet, Bouffard and colleagues (2017) point out use of little or no victim dialogue in RJIs, similar to the current study, shows improved recidivism outcomes compared to punitive interventions. Two more recent studies further highlight the benefits on reparation outcomes or plans to engage in other RJIs when using “surrogate” victims or no victim dialogue in RJIs (Hobbs et al, 2021; Weimann-Saks & Peleg-Koriat, 2020). Overall, our findings complement the body of literature focusing on alternative implementation methods of RJIs and suggest lack of dialogue does not preclude benefits of increasing victim awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, forgiveness therapy in a maximum-security facility was found effective as a stand-alone treatment or as an addition to traditional correctional rehabilitation approaches in reducing anger, depression, and anxiety and in increasing empathy (Enright et al, 2016; Yu et al, 2021). Moreover, prisoners who were exposed to a victim awareness procedure were more aware of the harm caused to the victim and demonstrated more favorable attitudes toward participating in a restorative-justice process (Weimann-Saks & Peleg-Koriat, 2020). Thus, forgiveness of others predicted self-forgiveness (Krentzman et al, 2018) and self-forgiveness was found effective in leading prisoners to become better people (Song et al, 2020), and those who have experienced the emotional consequences of their deeds, which facilitated self-work toward responsibility-taking (Woodyatt et al, 2017).…”
Section: Spiritual Companionship With People Who Offendedmentioning
confidence: 99%
“…In addition, feelings of regret and remorse mediated the correlation between guilt proneness and willingness to participate in an RJ process. Our goal in Study 2 was to replicate Study 1 and conduct an experiment to test, for the first time, the effect of guilt and shame proneness on the effectiveness of the preparatory RJ practice of victim awareness found effective in a previous study (Weimann-Saks & Peleg-Koriat, 2020).…”
Section: Studymentioning
confidence: 99%